2011
DOI: 10.4018/jsita.2011040102
|View full text |Cite
|
Sign up to set email alerts
|

Capability Development of Customers

Abstract: This paper identifies the application of capability concept (Sen, 2000) as a globally viable business strategy for the coming age which can be used to expand markets into to all levels of the social stratum. ‘Capability’ development is proposed as a way to propel business and expand markets to all levels of the social stratum. The article describes how Information and Communication Technology will create the buying power at the bottom of the pyramid and convert this stratum into a market as well as achieve soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…If they are customer and develop their capability through the usage of Information and Communication Technology which will create the buying power at bottom of pyramid and converts this stratum into a market as well as social development. Sharma et al (2011) revealed in their study that, how ICT can create the buying power at the BoP and convert this level into a market and achieve social development as well. ITC implemented their unique business venture e-Choupal so as to develop the capability of its customer by providing freedom, however projects like TATA literacy that cannot develop the market directly but unquestionably develops there capability.…”
Section: An Overview Of the Literaturementioning
confidence: 99%
“…If they are customer and develop their capability through the usage of Information and Communication Technology which will create the buying power at bottom of pyramid and converts this stratum into a market as well as social development. Sharma et al (2011) revealed in their study that, how ICT can create the buying power at the BoP and convert this level into a market and achieve social development as well. ITC implemented their unique business venture e-Choupal so as to develop the capability of its customer by providing freedom, however projects like TATA literacy that cannot develop the market directly but unquestionably develops there capability.…”
Section: An Overview Of the Literaturementioning
confidence: 99%